Kecerdasan Emosional Dalam Manajemen Pengambilan Keputusan - Laoli, Briyan Wirawan Putra; Waruwu, Demi Etika; Lase, Candra Eka Trisno (CV. SINAR HOWUHOWU, 2025)
Emotional intelligence has a substantial impact in management decision making, particularly at the individual and the organizational levels. This research aims to determine the importance of emotional intelligence in management decision making. Through a comprehensive literature review, this research will identify how emotional intelligence influences the decision-making process. Using a qualitative method, this examination gathers data from several studies in the few decades. Data sources in this research are obtained from journal articles, books, research reports and other scientific sources relevant to the research topic. The research results found that there are 4 roles of emotional intelligence in decision-making management, namely, integrity, strategic thinking, individual existence, and effective decisions. By managing emotions, both in oneself and in others, individuals can make better, wiser and more effective decisions that ultimately contribute to success. Controlling emotions in decision-making management does not mean suppressing or ignoring emotions, but rather understanding and managing them in a constructive way.